PENGGUNAAN DIRECT INSTRUCTION MODEL UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI TUMBUHAN DAN FUNGSINYA SISWA KELAS IV A SDN 015 SUNGAI SALAK KECAMATAN TEMPULING - Garnawati Siregar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
Problems in the Classroom Action Research (PTK) is the low learning outcomes IPA A fourth grade students of SDN 015 Sungai Salak Kecamatan Tempuling. This study addressed the problem by applying direct instrucsion models. The problem of this research is